p66Shc Deficiency in Chronic Lymphocytic Leukemia Promotes Chemokine Receptor Expression Through the ROS-Dependent Inhibition of NF-κB - Tatangelo, Vanessa; Boncompagni, Gioia; Capitani, Nagaja; Lopresti, Ludovica; Manganaro, Noemi; Frezzato, Federica; Visentin, Andrea; Trentin, Livio; Baldari, Cosima T.; Patrussi, Laura (Frontiers in Oncology, 2022)
The microenvironment of lymphoid organs is central to the pathogenesis of chronic lymphocytic leukemia (CLL). Within it, tumor cells find a favourable niche to escape immunosurveillance and acquire pro-survival signals. We have previously reported that a CLL-associated defect in the expression of the pro-apoptotic and pro-oxidant adaptor p66Shc leads to enhanced homing to and accumulation of leukemic cells in the lymphoid microenvironment. The p66Shc deficiency-related impairment in intracellular reactive oxygen species (ROS) production in CLL cells is causally associated to the enhanced expression of the chemokine receptors CCR2, CXCR3 and CCR7, that promote leukemic cell homing to both lymphoid and non-lymphoid organs, suggesting the implication of a ROS-modulated transcription factor(s). Here we show that the activity of the ROS-responsive p65 subunit of the transcription factor NF-B was hampered in the CLL-derived cell line MEC-1 expressing a NF-B-luciferase reporter following treatment with H2O2. Similar results were obtained when intracellular ROS were generated by expression of p66Shc, but not of a ROS-defective mutant, in MEC-1 cells. NF-B activation was associated with increased expression of the chemokine receptors CCR2, CXCR3 and CCR7. Reconstitution of p66Shc in CLL cells normalized intracellular ROS and hampered NF-B activation, which led to a decrease in the expression of these homing receptors. Our data provide direct evidence that the p66Shc-deficiency-related ROS depletion in CLL cells concurs to NF-B hyperactivation and homing receptor overexpression, providing a mechanistic basis for the enhanced ability of these cells to accumulate in the pro-survival lymphoid niche.